Factors Affecting Travel Intention of Citizens of Pakistan via Premium Bus Services: A Case Study - Rana , Freeha; Ameen, Yasir (Pakistan Journal of Humanities and Social Sciences, 2023)
This study explores the impact of tourism related variables such as service quality, environmental concern, corporate reputation, word-of-mouth and travel intention on Pakistan's premium bus services. Data is collected through questionnaires and convenience sampling is used. For data analysis, SPSS and Smart PLS3 software are used. Theoretical results vindicated a positive relationship between travel intention and service quality as well as corporate reputation. This study identifies the positive relationship between corporate reputation and service quality with travel intention via premium bus services whereas travel intention has also the significant relationship with word of mouth and environmental concern. Pakistan has huge potential for tourism, and the government should focus on promoting it through measures such as improving infrastructure, fostering safety and security, highlighting its strengths, and showcasing environmental responsibility. By doing so, Pakistan can emerge as a major player in the tourism industry, drive its economic growth and it helps the customers to decide their tourism plans.